A novel digital health intervention to improve patient engagement to stimulants in adult ADHD in the primary care setting: Preliminary findings from an open label study. (September 2020) - Biederman, Joseph; Fried, Ronna; DiSalvo, Maura; Driscoll, Haley; Green, Allison; Biederman, Itai; Woodworth, K. Yvonne; Faraone, Stephen V.
Highlights: Adults with ADHD who received a text messaging (SMS)-based intervention aimed at improving adherence to stimulant medication had significantly higher rates of adherence compared to adults receiving treatment as usual. The difference in stimulant medication adherence rate between the SMS group and the treatment as usual group did not significantly differ by prescribing clinic (psychiatry versus non-psychiatry). Digital health interventions are accessible, inexpensive, and provide opportunity for educational and motivational content that can help primary care physicians in their efforts to educate and support patients with ADHD. Abstract: Aims: We piloted the effectiveness and acceptability of a novel text messaging-based (SMS) digital health intervention aimed at addressing the previously documented poor rate of patient engagement in stimulant treatment in the primary care setting. Methods: 117 adults ages 18–55 from primary care and psychiatric practices who were prescribed a stimulant medication for ADHD treatment received the SMS intervention. Comparators were age-, race-, and sex-matched patients from the same health care organization's electronic medical record who had been prescribed stimulant medications over a similar time period. Using documented prescription records, we determined whether patients had timely prescription refills. Results: Ninety-six percent ( N  = 112) of participants completed our a priori metric of patient engagement consisting of 37 days of the SMS program. Eighty-one percent of participants refilled their index prescriptions in a timely manner compared to only 36% of patients receiving treatment as usual (OR=7.54, 95% CI: 4.46, 12.77; p <0.001). We found no significant interaction between prescribing source (non-psychiatry vs. psychiatry) and intervention group (SMS vs. treatment as usual). Conclusions: These data suggest that an ADHD-centric, digital health intervention using text messaging significantly improves patient engagement in stimulant treatment in adults with ADHD.